Neuroendocrine cancer of maxillary sinus: case report and literature review - T. I. Deshkina; L. V. Bolotina; A. R. Gevorkov; A. V. Boyko; V. S. Surkova; M. V. Sedova; A. P. Polyakov; A. L. Kornietskaya; A. A. Fedenko (Опухоли головы и шеи)
Malignant tumors of the sinuses and nasal cavity are rare diseases. Squamous cell carcinoma is the most common histological type (55–70 % of tumors of the sinuses and nasal cavity). The frequency of neuroendocrine tumors reaches 5 %. Currently, there is no generally accepted standard for the treatment of neuroendocrine tumors of sinonasal localization. If surgical treatment is associated with a significant deterioration of the quality of life or poor outcomes, chemoradiotherapy can be recommended. This article describes a clinical case of combined treatment of neuroendocrine cancer of the maxillary sinus and brief review of the literature on malignant tumors of the paranasal sinuses and the nasal cavity.